2018
DOI: 10.3390/ijerph15061194
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Socioeconomic Status in the Patients with Rheumatoid Arthritis

Abstract: Rheumatoid arthritis (RA) is a systemic inflammatory disease with different etiologies in different areas. Our study focused on the prevalence of RA in Taiwan from 2001 to 2011. This study contained longitudinal enrollment files, claims data, catastrophic illness files, and treatment registries from Taiwan Longitudinal Health Insurance Research Database. We identified RA patients by ICD-9-CM code 714.0. The demographical variables including age, sex, income and area of registration were evaluated. The multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 26 publications
3
34
0
Order By: Relevance
“…Therefore, the damage of SLE which might influence the patients’ ability of work was minimized. Another study about the socioeconomic status of rheumatoid arthritis patients published in 2018 also used this definition for economic levels 21 . Our study suggested that the prevalence and incidence for SLE is lower in higher income levels group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the damage of SLE which might influence the patients’ ability of work was minimized. Another study about the socioeconomic status of rheumatoid arthritis patients published in 2018 also used this definition for economic levels 21 . Our study suggested that the prevalence and incidence for SLE is lower in higher income levels group.…”
Section: Discussionmentioning
confidence: 99%
“…The level of urbanization was originally divided into seven categories according to demographic components in communities. In this study, urbanization was regrouped into three levels (urban, suburban, and rural areas), as in previous studies 13 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was in line with previous finding. 32 In this study, industry workers, housewives, farmers, government civil servants, and private workers were involved to assess their disease activity status (Figure 1). The result of our study agreed with previous data.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive joint damage, pain, disability, and premature mortality are hallmarks of RA, particularly if not treated early and appropriately [3]. Environmental and socioeconomic factors may also influence disease status [4]. Patients often suffer from symptoms that may be objectively difficult to quantify (e.g., fatigue), while they impact work performance, and are often disregarded by employers [5].…”
Section: Introductionmentioning
confidence: 99%